Characterization of the thermal and mechanical properties of additively manufactured carbon fiber reinforced polymer exposed to above-zero and sub-zero temperatures - Isyna Izzal Muna; Magdalena Mieloszyk; Ruta Rimasauskiene (Journal of Materials Research and Technology)
This experimental work aims to study the thermal degradation of carbon fiber reinforced polymer (CFRP) printed using additive manufacturing. The printed samples were exposed to various thermal modes (prolonged and cyclic) and magnitudes (above- and sub-zero degrees). The influence of temperature on CFRP was investigated using static tensile testing (Young's modulus and tensile strength) supported by scanning electron microscope and differential scanning calorimetry. It is revealed that Young's modulus and tensile strength of samples were all degraded after all thermal treatments. Observing the morphological structure on the surface revealed changes in the degradation processes due to thermal treatments. A list of the dominant degradation types for each analysed thermal treatment is presented in the paper. It was observed that similar mechanical parameters values can be linked with different material degradation processes.